2002
DOI: 10.2190/9jw6-vv1p-fax8-cge0
|View full text |Cite
|
Sign up to set email alerts
|

Do Male Students Often Perform Better Than Female Students When Learning Computers?: A Study of Taiwanese Eighth Graders' Computer Education through Strategic and Cooperative Learning

Abstract: This study investigated the impacts of strategic learning, cooperative learning, and their combination on junior high school students' computer achievement, attitudes, and anxiety. A total of 155 Taiwanese eighth graders participated in this study. Regarding computer achievement, a significant interaction was found between gender and learning context. No significant difference was found in students' computer attitudes due to either learning context or gender factor. With respect to computer anxiety, however, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 27 publications
0
22
0
2
Order By: Relevance
“…It requires to be complemented by other methods such as interviews, user logs, or ethnographic studies in the future. Future study should also be conducted to further examine the impact of teaching learning strategies on students' computer achievement, attitude, and anxiety, especially for those significant-correlated learning strategies identified in this study (Tsai, 2002). Furthermore, this study is only an initial attempt to explore computer domainspecific learning strategies.…”
Section: Discussionmentioning
confidence: 97%
“…It requires to be complemented by other methods such as interviews, user logs, or ethnographic studies in the future. Future study should also be conducted to further examine the impact of teaching learning strategies on students' computer achievement, attitude, and anxiety, especially for those significant-correlated learning strategies identified in this study (Tsai, 2002). Furthermore, this study is only an initial attempt to explore computer domainspecific learning strategies.…”
Section: Discussionmentioning
confidence: 97%
“…Finally, a number of researchers have focused on gender differences in Internet use, interest and attitudes (e.g., Colley, 2003;Colley & Comber, 2003;Durndell & Haag, 2002;Jackson, Ervin, Gardner, & Schmitt, 2001;Kadijevich, 2000;Madell & Muncer, 2004;Nachmias, Mioduser, & Shemla, 2000;Schumacher & Morahan-Martin, 2001;Shaw & Gant, 2002;Tsai, 2002;and Weiser, 2000). Nachmias and colleagues (2000) found that more males than females used the Internet.…”
Section: Barriers To Enrollment In Internet Trainingmentioning
confidence: 99%
“…Published definitions or explanations of general computer literacy 9,19,22 were not considered in the articles reviewed. Oenema and colleagues 33 defined computer literacy as the sum of individuals' frequency and ease of computer use; Thumboo et al 32 presented a scale which seemed to measure computer skills but was also referred to as a measure of computer literacy.…”
Section: Discussionmentioning
confidence: 99%
“…Computer literacy has been defined as the ability to interact with a computer 9 or 'basic knowledge, skills, and attitudes needed by all citizens to be able to deal with computer technology in their daily life' 19 . Advancements in new information technologies have contributed to innovation in the way we work, communicate and seek out information.…”
mentioning
confidence: 99%